Inhibition of Degranulation of RBL-2H3 Cells by Extracts and Compounds from Armillaria ostoyae - Merdivan, Simon; Jenett-Siems, Kristina; Siems, Karsten; Niedermeyer, Timo; Solis, Michael J.; Unterseher, Martin; Lindequist, Ulrike (Planta Medica International Open, 2017)
Armillaria ostoyae (Romagn.) Herink is an edible honey mushroom from the family Physalacriaceae (Agaricales, Basidiomycota). Dichloromethane extracts of mushroom mycelium and fruiting bodies exhibited a significant degranulation inhibiting effect on RBL-2H3 cells using noncytotoxic concentrations. Bioactivity-guided fractionation of the mycelial dichloromethane extract led to the isolation of sesquiterpen aryl esters. Methyl linoleate could also be isolated. These substances were obtained from A. ostoyae for the first time, with one compound representing an undescribed natural product. Purified compounds melleolide H and J inhibited degranulation significantly. A. ostoyae could be a candidate for support of allergy treatments.
Keywords: Armillaria ostoyae; Physalacriaceae; RBL-2H3; sesquiterpene aryl esters; β-hexosaminidase assay; melleolide; cytotoxicity